A Cultural Approach (Socio Demography) in Preventing Covid-19 Disease in the Family - Khairir Rizani; Bisepta Prayogi; Angga Irawan; Taufik Hidayat (STIKes Patria Husada Blitar, 2022)
Handling the Covid-19 pandemic can be assisted by a cultural approach as disease and culture are two related things, disease is often caused by culture or in other words, disease can occur due to certain cultures that exist in social life. In addition, the disease can have a socio-cultural effect. Thus, socio-cultural factors generally affect efforts to control and prevent Covid-19 disease. In addition, the involvement of the family in the control and prevention of Covid-19 is very important, in addition to controlling the transmission, it also stabilizes the control of the spread of the virus. The aim of this study was to identify the influence of culture on the prevention of Covid-19 in the family. This study used an associative analytical design through a transversal approach. The population consisted of all families affected by the Covid-19 case in South Kalimantan. Bivariate data were analyzed with chi-squared and multivariate with multiple logistic regression. There was a relationship between sex, education, marriage, occupation, income and distance from health services with the prevention of covid 19 in the family (Ï <0.05), and there is a shared influence between gender, education, marriage and work on the prevention of covid 19 in the family (Ï <0.05). It is up to the community to redouble its efforts to prevent covid 19 disease in the family, so it is necessary to take a cultural approach to prevent covid 19 in the family.